Trypanotolerance Sheko cattle: an option for sustainable control of bovine trypanosomiasis - Robi Dereje Tulu; Hurrisa Beksisa Urge; Gelalcha Benti Deresa (Open Veterinary Science, 2021)
Trypanosomiasis is an impediment to cattle production and other agricultural development in tsetse-infested areas. It is a severe parasitic disease that causes loss in the production and performance of cattle. Hence, the aim of this paper is to review trypanosomiasis control options with emphasis on the use of trypanotolerant Sheko cattle breed for sustainable management of bovine trypanosomiasis in tsetse infested areas. Several methods have been used to control trypanosomiasis through the use of trypanocidal drugs and the management of the vector, tsetse fly. Tsetse fly controls require expensive insecticides and have adverse environmental consequences. Trypanocidal drugs are commonly used and considered a practical trypanosomiasis control method. However, the rise in trypanocidal drug resistance has rendered this option ineffective. The possibility of developing and using a vaccine against trypanosomiasis currently remains out of reach as Trypanosoma periodically undergo antigenic variation. In the absence of a vaccine, presence of trypanocidal drug resistance, and the lack of sustainable tsetse fly control measures demand the need to use trypanotole-rant cattle breeds. The Sheko breed which is found only in southwestern Ethiopia displays considerable natural resistance to tsetse-transmitted trypanosomiasis. This genetic resource provides sustainable solution for challenges related to trypanosomiasis. These cattle have a low level of parasitemia and are able to maintain a good packed cell volume (PCV) compared to other indigenous breeds. As several trypanosomiasis control methods are ineffective, the use of trypanotolerance cattle like Sheko breed in tsetse-fly-challenged areas was suggested.